Societal impact of university innovation. Issue 11 (19th November 2018) - Yeo, Benjamin
Abstract : Purpose: This study aims to use university patent and regional economic data to investigate the current and future impact of university innovation, measured using multiple variables, on real economic productivity. Design/methodology/approach: Using university patent and regional economic data, regression models are built to determine the impact of university innovation on current and future regional economic performance. Findings: The findings demonstrate that university innovation generates sustained impact on economic performance, but by itself, is insufficient in driving economic performance; and different measures of university innovation have different degrees of impact. University innovation makes up a small, albeit significant, proportion of the drivers of economic performance. Research limitations/implications: There are four implications. First, developing countries can leverage university–industry collaborations for economic growth. Second, innovation management must encourage continuous university innovation for sustainable economic productivity. Third, Science, Technology, Engineering and Mathematics (STEM) and non-STEM innovation warrant attention. Fourth, successful innovation policies should be tailored to their unique societal contexts. Originality/value: Although innovation is a driver of economic performance, there is a lack of studies that focus specifically on universities, operationalize performance using gross domestic product measures and take into account impact lags by exploring universities' current and future impacts.